New and growing firms' entrepreneurs' perceptions and their discriminant power in EDL countries. (6th March 2019) - Pilar, Maria De Fátima; Marques, Mariana; Correia, Aldina
This work aims to analyse entrepreneur's perceptions about conditions to create new and growing firms and their significance in the economic development level (EDL) of countries. For this paper was used Global Entrepreneurship Monitor (GEM) project, in particular, the dataset NES 2013. To group the variables related to entrepreneur's perceptions about conditions to create new and growing firms a factor analysis was done and the variables more relevant are identified. Eight factors were obtained and renamed considering the entrepreneurial framework conditions (EFCs) defined by GEM. Next, in order to find out which variables contributed to economic development level of the countries, considering the entrepreneurs' perceptions, a discriminant analysis was carried out. With this study, we conclude that the levels of economic development are distinguished by the perceptions of entrepreneurs about new and growing firms.